Leg Cramps, Its Associated Factors And Quality Of Life Among Pregnant Mothers: A Cross-sectional Study In A Malaysian Suburban Health Clinic - Sharifah Najwa Syed Mohamad; Saharuddin Ahmad; Hizlinda Tohid (JK Welfare & Pharmascope Foundation, 2024)
Leg cramps (LCs) are common in pregnancy and may affect pregnant mothers’ quality of life (QoL). However, studies to show this impact are still lacking. Thus, this study aimed to evaluate the association of LCs with QoL among pregnant mothers. The magnitude and characteristics of LCs were assessed too. A cross-sectional study was conducted at a government health clinic in Hulu Langat, Selangor involving 99 mothers in their second or third trimesters, recruited through convenience sampling between March and April 2018. This study used a developed bilingual (Bahasa Malaysia and English) self-administered questionnaire on leg cramps proϐile, as well as the bilingual self-administered SF-12v2, to assess their QoL. About 71.7% experienced LCs during this pregnancy. About half experienced LCs once to twice a week and 63.4% had moderately painful LCs. Only 26.7% had severely painful LCs and 12.7% had the next-day soreness in all or most of the time. Gestational age (P=0.001) and booking Body Mass Index (BMI) (p=0.022) were signiϐicantly associated with LCs, but not their QoL (p=0.712 for PCS and p=0.118 for MCS). Generally, LCs were common among these pregnant mothers. However, LCs appear to be brief, infrequent, and mild which did not signiϐicantly affect their QoL. Nevertheless, LCs should not be disregarded, as a subgroup of them experienced severe LCs with the next day soreness who may need further assessment and treatment.